Political participation of women. Political and partisan progress and challenges in Santa Fe Province (Papeles, 2023)
Despite the fact that women have achieved influential roles in both, the international and national arenas, much work remains. There have been many paradigm shifts over the last thirty years. However, a significant portion of the activities in our society still leans more toward the masculine, even, if we consider activities related to public and political life. Consequently, the possibility of improving paritarian democracy is limited under these circumstances. This paper aims to identify the democratic subnational affirmative action programs, considering beforehand the challenges that women may face in the future.
Keywords: Affirmative actions; paritarian democracy; democratic quality; legislative power; Santa Fe